MEASUREMENT OF WETLAND PENETRATION RESISTANCE AT VARIOUS POINTS OF PRESSURE - Z.F. Nizamani; Irwin Syahri Cebro (Nusa Putra University, 2018)
Traction performance of a cage wheel for two-wheel tractor depended on its shape, dimension, lugs materials and soil condition. In order to get the optimum design of the cage wheel, relation between tractor, implement and soil condition should be considered carefully. The objective of this research was to determine optimum design parameters of cage wheel for the farm field in North Aceh. A computer program for design analysis and for producing engineering drawing of cage wheels. The computer program was developed and employed for the optimization process and for drawing the design result. As a trial of the program, the optimum design parameters of cage wheel were found to be: 75 cm of wheel diameter; 8 lugs; 19 cm × 10 cm of lug size; and 30° of lug angle. The result of field testing (validation) shown that wheel of a tractor using the design was able to work well and it can produce ground-level of muddy better than the standard wheel.